STEM-Based CNC Advanced Learning Material: Integration of CNC Milling and Plasma Cutting Using Mastercam for Vocational Education - Rudi Hermawan; Ainun Maulidina; Yogi Herdianto; Romy Saputra; Ahmad Hafiz Addin; Median Tara; Rani Oktapiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This research aims to develop valid and practical Advanced CNC teaching materials based on Mastercam-assisted STEM for the Advanced CNC course. Using the ADDIE development model Analyze, Design, Develop, Implement, and Evaluate these teaching materials are designed to integrate CNC Milling and Mastercam-assisted Plasma Cutting materials, while enhancing the 4C skills (communication, collaboration, critical thinking, and creativity). Validation by material and media experts yielded average scores of 4.00 and 3.89, respectively, categorized as excellent. A field trial involving 39 students yielded a practicality score of 3.63, indicating excellent/practical usability.For the 4C skills, the communication aspect achieved 82%, collaboration 87%, critical thinking 92%, and creativity 88%. These results confirm that the developed teaching materials meet the criteria for validity and practicality. With a high N-Gain improvement, the teaching materials are proven to be effective in supporting learning oriented towards industry needs and modern manufacturing technology.